3D Printed E-Band Hybrid Coupler - Lomakin, Konstantin; Klein, Laura; Ringel, Lorenz; Ringel, Johannes; Sippel, Mark; Helmreich, Klaus; Gold, Gerald (IEEE Microwave and Wireless Components Letters, 2019)
In this work, an additively manufactured 3dB hybrid coupler is presented. While the geometrical structure is generated by an SLA printer from UV curable photopolymer resin as one single part, conductive coating is provided by an electroless silverplating process. The utilized slotted waveguide approach improves the solvent flow during metal plating and therefore enables the fabrication of complex waveguide struc- tures. Measured imbalance between the through and coupling port stays below 1.5dB over the entire E-Band, while the respective phase difference ranges only between 87◦ and 91◦ degrees despite the challenges of additive manufacturing in such frequency regions

Evaluation and Characterization of 3D Printed Pyramid Horn Antennas utilizing different Deposition Techniques for Conductive Material - Lomakin, Konstantin; Pavlenko, Tatiana; Ankenbrand, Markus; Sippel, Mark; Ringel, Johannes; Scheetz, Matthias; Klemm, Tobias; Gräf, Daniel; Helmreich, Klaus; Franke, Jörg; Gold, Gerald (IEEE Transactions on Components, Packaging and Manufacturing Technology, 2018)
This paper evaluates different metal deposition approaches for a two-staged additive manufacturing (AM) process for 3-D horn antennas, divided into the deposition of plastic and conductive material. The demonstrated fabrication workflow allows for antennas of low cost and low weight and, therefore, demonstrates the vast benefit of AM. The comparison of a commercially available cast aluminum horn to the fabricated prototypes reveals a deviation of up to 3 dB in terms of transmission losses in copolarization over a distance of 1.85 m. Cross-polarization measurements are presented revealing a larger variation among the different metallization approaches. The results shown in this paper demonstrate a successful application of AM in radio frequency engineering. Moreover, one of the presented approaches makes use of only 3-D printing systems and is, therefore, potentially suitable for totally automated manufacturin
lhft_intern.bib::Lomakin2018g

Nearfield imaging probe for contactless assessment of burned skin - Oppelt, Daniel; Pfahler, Tim; Distler, Felix; Ringel, Johannes; Goertz, Ole; Vossiek, Martin (13th European Radar Conference (EuRad), 2017)
In modern burn surgery the fast and precise assessment of the burn depth is challenging but also of high importance to adapt the correct wound care. A contactless nearfield probe operating at frequencies from 75 to 110 GHz is presented that is sensitive to the hydration of the skin layers, which is correlated to the burn depth. The results of an in-vivo human skin measurement are presented and a corresponding simulation is adapted that enables a contactless estimation of hydration of stratum corneum and epidermis/dermis as well as its thickness. A millimeter wave image of ex-vivo burned porcine skin is created by positioning the probe stepwise in front of the target to exemplary illustrate the potential of nearfield probe imaging for burn diagnosi

SLA Printed 3D Waveguide Paths for E-Band using Electroless Silver Plating - Lomakin, Konstantin; Herold, Sophie; Ringel, Lorenz; Ringel, Johannes; Simon, D.; Sippel, Mark; Sion, A.; Vossiek, Martin; Helmreich, Klaus; Gold, Gerald (IEEE Transactions on Components, Packaging and Manufacturing Technology, 2019)
This work proposes a fabrication approach for 3D printed waveguide paths based on a combination of an optimized electroless silver plating process with a waveguide-specific design rule for general metal plating by introducing large scale non- radiating slots into the broad and narrow waveguide walls with a periodicity shorter than quarter of the guided wavelength. Experimental fabrication of straight sections of the proposed slotted waveguide with various gap dimensions yields an optimum gap size as result of a trade-off between silver plating quality and leakage losses through the sidewall gaps. Moreover, a successful practical application of the proposed approach is presented in terms of a 3D printed multiple bend waveguide interconnect in three different space dimensions which imposes a complex task for conventional manufacturing tech- niques due to the need of multiple cutting planes for split block assembly. The proposed approach benefits of low cost, moderate handling effort and independence of the concrete geometry to manufacture making it therefore especially interesting for distri- bution and feeding networks in the context of rapid prototyping, automotive and space related applications

Substituting bond wires by additively manufactured interconnections - Lomakin, Konstantin; Sippel, Mark; Gold, Gerald; Ringel, Johannes; Weiß, David; Helmreich, Klaus; Ankenbrand, Markus; Franke, Jörg (German Microwave Conference, 2018)
This work shows a comparison of microstrip to integrated circuits junction between conventional bond wires and additively manufactured signal interconnect. Therefore, an approach for reducing signal reflection is proposed and implemented on a test board fabricated on typical radio frequency substrate material. Measurements up to 24 GHz reveal improved performance as compared to conventional technology in terms of reflection suppression and transmission losse